Risk factors influencing caesarean wound infection (CWI) - Yolanda Salsabila Dwi Putri; Reeny Purnamasari Juhamran; Ronaldo August Rambulangi; Nasrudin Andi Mappaware; Muhammad Wirawan Harahap (Malahayati International Journal of Nursing and Health Science, 2025)
Background: Cesarean section (CS) is a delivery method that continues to increase and carries a risk of complications, one of which is surgical wound infection (SWI). SWI can hinder healing and increase morbidity. Risk factors for infection include preoperative, intraoperative, and postoperative conditions, necessitating analysis to prevent postoperative complications. Purpose: To identify risk factors for surgical site infection in Cesarean section procedures and to determine the association between nutritional status, hemoglobin levels, and wound care with the occurrence of surgical site infection. Method: This study is an observational analytical study using a cross-sectional approach conducted at RSIA Sitti Khadijah 1 Muhammadiyah Makassar from March to June 2025. Data were analyzed using univariate and bivariate analysis with the Chi-square test at a significance level of p < 0.05. Results: There was a significant association between several risk factors and the occurrence of postoperative wound infections following Cesarean section. Based on bivariate analysis, nutritional status, hemoglobin (Hb) levels, wound care, and type of cesarean section procedure were found to influence the occurrence of postoperative wound infections. However, although the duration of surgery showed a statistical association, the data obtained were not varied, so a definitive conclusion regarding the relationship between surgery duration and postoperative wound infections after cesarean section could not be drawn. Conclusion: Nutritional status, hemoglobin levels, wound care, and type of cesarean section are factors associated with the occurrence of postoperative wound infections after cesarean section. These findings highlight the importance of attention to maternal nutritional status, hemoglobin levels, wound care standards, and the selection of Cesarean section type in efforts to prevent postoperative infections. A comprehensive evaluation of these factors is necessary to minimize the risk of complications and improve patient safety.